Pengenalan Teknologi Kendaraan Listrik untuk Siswa Sekolah Menengah Pertama (SMP) - Hari Maghfiroh; Feri Adriyanto; Augustinus Sujono; Joko Slamet Saputro; R Lulus Lambang GH (Universitas Mathla'ul Anwar Banten, 2021)
INTRODUCTION TO ELECTRIC VEHICLE FOR JUNIOR HIGH SCHOOL STUDENTS. The purpose of this service program is to introduce junior high school students to electric vehicle technology. The material presented is basic material covering the meaning, benefits, and components of electric vehicles. The socialization was carried out via online due to the corona outbreak. The explanation is done with a short video consisting of a simple explanation as well as a demo of the components of a real electric vehicle with an electric bicycle. In addition, students are also given a short ebook on the material. To find out students' understanding, a short quiz about the material was given. The result is an average score of 83.9%, which indicates that the participants' level of understanding is quite good with the material presented. The sample of basic questions about electric vehicles showed that only 3.8% of students were wrong. In the final conclusion, students have gained knowledge about electric vehicles through socialization activities that have been carried out.